Myocardial injury after noncardiac surgery—incidence and predictors from a prospective observational cohort study at an Indian tertiary care centre. Issue 19 (May 2018) - George, Rubin; Menon, Vidya P.; Edathadathil, Fabia; Balachandran, Sabarish; Moni, Merlin; Sathyapalan, Dipu; Prasanna, Preetha; S, Gokuldas; Paul, Jerry; K.K., Chandrababu; Kumar, Lakshmi; Pillai, Ashok
Abstract : Abstract: Asymptomatic myocardial injury following noncardiac surgery (MINS) is an independent predictor of 30-day mortality and may go unrecognized based on standard diagnostic definition for myocardial infarction (MI). Given lack of published research on MINS in India, our study aims to determine incidence of MINS in patients undergoing noncardiac surgery at our tertiary care hospital, and evaluate the clinical characteristics including 30-day outcome. The prospective observational study included patients >65 years or >45 years with either hypertension (HTN), diabetes mellitus (DM), coronary artery disease (CAD), cerebrovascular accident (CVA), or peripheral arterial disease undergoing noncardiac surgery. MINS was peak troponin level of ≥0.03 ng/dL at 12-hour or 24-hour postoperative. All patients were followed for 30 days postoperatively. Predictors of MINS and mortality were analyzed using multivariate logistic regression. Patients categorized based on peak troponin cut-off values determined by receiver operating characteristic curve were analyzed by Kaplan–Meir test to compare the survival of patients between the groups. Among 1075 patients screened during 34-month period, the incidence of MINS was 17.5% (188/1075). Patients with DM, CAD, or who underwent peripheral nerve block anaesthesia were 1.5 ( P <  .01), 2 ( P <  .001), and 12 ( P <  .001) times, respectively, more likely to develop MINS than others. Patients with heart rates ≥96 bpm before induction of anesthesia were significantly associated with MINS ( P =  .005) and mortality ( P =  .02). The 30-day mortality in MINS cohort was 11.7% (22/188, 95% CI 7.5%–17.2%) vs 2.5% (23/887, 95% CI 1.7%–3.9%) in patients without MINS ( P <  .001). ECG changes ( P =  .002), peak troponin values >1 ng/mL ( P =  .01) were significantly associated with mortality. A peak troponin cut-off of >0.152 ng/mL predicted mortality among MINS patients at 72% sensitivity and 58% specificity. Lack of antithrombotic therapy following MINS was independent predictor of mortality ( P <  .001), with decreased mortality in patients who took post-op ASA (Aspirin) or Clopidogrel. Mortality among MINS patients with post-op ASA intake is 6.7% vs 12.1% among MINS patients without post-op ASA intake. Mortality among MINS patients with post-op Clopidogrel intake is 10.5% vs 11.8% among MINS patients without post-op Clopidogrel intake. A higher (17.5%, 95% CI 15–19%) incidence of MINS was observed in our patient cohort with significant association with 30-day mortality. Serial postoperative monitoring of troponin following noncardiac surgery as standard of care, would identify "at risk" patients translating to improved outcomes. Abstract : Supplemental Digital Content is available in the text